A Descriptive Study On English Spelling Mastery In Listening Class Of The Eight Year Students SMP Muhammadiyah 2 Karanganyar In 2014 - Nikmah., Azizatun, Drs. Djoko Srijono, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
This research paper is conducted to know the spelling mastery of the students in SMP Muhammadiyah 2 Karanganyar. It aims at describing the spelling ability on listening class at SMP Muhammadiyah 2 Karanganyar. The purpose of this research is describe the spelling mastery of the students and the problem faced by the students in spelling. The writer takes the students of second class as subject of the study. The primary data are mainly taken from test. The second data are obtained from interview with the students. In collecting the data, the writer uses descriptive method that consists of test and interview. Meanwhile, the data are analyzed by using descriptive research. The result of the research is the spelling ability on English listening class of the eight year students of SMP Muhammadiyah 2 Karanganyar is still poor. The problems faced by the students in spelling in SMP Muhammadiyah 2 Karanganyar are: 1) they are unfamiliar with the new vocabulary, 2) Students' ability in receiving listening materials is not good, 3) Students are mispronouncing the words spoken by the teacher.